Ù…Ù†Ù‡Ø¬ Ù…Ù‚ØªØ±Ø Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…Ù„Ø§ÙˆÙŠØ© Ø§Ù„Ù…Ù‚ØªØ±Ø¶Ø© Ù„ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ø¯Ù‰ Ø§Ù„Ù…Ù„Ø§ÙŠÙˆÙŠÙŠÙ† Ø§Ù„Ù…Ø¨ØªØ¯Ø¦ÙŠÙ† - Fachrirazi, Fachrirazi (El-Hayah, 2021)
ABSTRACTThis study aims to know and find Malay words derived from Arabic in the DAYA dictionary. This research helps students learn Arabic indirectly using their language, so they can learn, memorize vocabulary and understand its meaning more easily. Researchers found two results: the first is the presence of Arabic words in the Daya dictionary and the number reaches around 184 words from the letter K to the letter M, and the second is through these Malay words, the teaching and learning process can be facilitated in designing a curriculum appropriate for the Malay community, and that is by using the words of Malay Language which originated from Arabic making it easier for Malay people to learn Arabic. This study includes four skills except for writing skills, and in them consists of; dialogues, vocabulary, exercises, and texts, as well as methods and methods in teaching Arabic to Malay beginners.Keywords: proposed curriculum, teaching Arabic, Malay words derived from Arabi